2008
DOI: 10.4049/jimmunol.180.8.5384
|View full text |Cite
|
Sign up to set email alerts
|

The Lymphotoxin Pathway Regulates Aire-Independent Expression of Ectopic Genes and Chemokines in Thymic Stromal Cells

Abstract: Medullary thymic epithelial cells (mTEC) play an important and unique role in central tolerance, expressing tissue-restricted Ags (TRA) which delete thymocytes autoreactive to peripheral organs. Since deficiencies in this cell type or activity can lead to devastating autoimmune diseases, it is important to understand the factors which regulate mTEC differentiation and function. Lymphotoxin (LT) ligands and the LTβR have been recently shown to be important regulators of mTEC biology; however, the precise role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(104 citation statements)
references
References 35 publications
8
95
1
Order By: Relevance
“…These mice have significantly reduced levels of Aire [20] and NKT cells [21,22], but relatively normal conventional T-cell numbers. A similar correlation between Aire expression and NKT cell numbers was reported in lymphotoxin-deficient mice [23,24], although the link between the expression of lymphotoxin and Aire-dependent genes has been disputed in more recent studies [25][26][27]. Human patients (and a mouse model) of Omenn syndrome [28,29] also have reduced levels of Aire and NKT cells and it is interesting to note that the severe NKT cell deficit evident in NOD mice coincides with significant morphological abnormalities among Aire 1 medullary cells in the thymus [20].…”
Section: Introductionsupporting
confidence: 55%
“…These mice have significantly reduced levels of Aire [20] and NKT cells [21,22], but relatively normal conventional T-cell numbers. A similar correlation between Aire expression and NKT cell numbers was reported in lymphotoxin-deficient mice [23,24], although the link between the expression of lymphotoxin and Aire-dependent genes has been disputed in more recent studies [25][26][27]. Human patients (and a mouse model) of Omenn syndrome [28,29] also have reduced levels of Aire and NKT cells and it is interesting to note that the severe NKT cell deficit evident in NOD mice coincides with significant morphological abnormalities among Aire 1 medullary cells in the thymus [20].…”
Section: Introductionsupporting
confidence: 55%
“…LT signaling culminates in nuclear translocation of the RelB/ p52 dimer and results in transcription of genes critical for maintenance of secondary lymphoid organs and the mTEC network, including CCL19, CCL21, and CXCL13 (34,45,70). In this model, the increase in CCL19 and CCL21 was most likely due to dysregulated transcription rather than to increased LT signaling, since these chemokines were not increased uniformly across mTEC subsets.…”
Section: Discussionmentioning
confidence: 90%
“…In the postnatal thymus, the cellularity of Aire 1 mTEC is controlled by cooperation of CD40 and RANK signals mainly provided by CD4 1 SP thymocytes [36][37][38]. The TNF-related cytokines, lymphotoxin LTa/LTb and LTbR have also been recently shown to influence the proper organization and differentiation of mTEC without affecting the expression of Aire [39]. Since we have shown that Spatial expression strongly differs between immature and mature mTEC, we can suggest that its expression could be controlled by any of those signaling pathways (Fig.…”
Section: Rank Signals Regulate Spatial Expression Through the Transcrmentioning
confidence: 99%